Detection and genotype of Rotavirus a from wastewater of Dhaka and Cox’s Bazar city - Salsabil, Parsha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.